2.1.5 Use \( \cos (\alpha-\beta) \) to derive a formula for \( \sin (\alpha-\beta) \). (Hint: use co-function) in degrees
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
To derive a formula for \( \sin (\alpha - \beta) \) using \( \cos (\alpha - \beta) \), we start with the co-function identity where \( \sin(\theta) = \cos(90^\circ - \theta) \). Thus, we have: \[ \sin(\alpha - \beta) = \cos(90^\circ - (\alpha - \beta)) = \cos(90^\circ - \alpha + \beta). \] Now, we can express \( \cos(90^\circ - \alpha + \beta) \) using the cosine angle subtraction formula: \[ \cos(90^\circ - \alpha + \beta) = \cos((90^\circ - \alpha) + \beta) = \cos(90^\circ - \alpha)\cos(\beta) - \sin(90^\circ - \alpha)\sin(\beta). \] Since \( \cos(90^\circ - \alpha) = \sin(\alpha) \) and \( \sin(90^\circ - \alpha) = \cos(\alpha) \), we substitute these into the equation: \[ \sin(\alpha - \beta) = \sin(\alpha) \cos(\beta) - \cos(\alpha) \sin(\beta). \] Therefore, we arrive at the derived formula: \[ \sin(\alpha - \beta) = \sin(\alpha) \cos(\beta) - \cos(\alpha) \sin(\beta). \]